(untitled) (Lapai Journal of Economics, 2022)
This study examined the effect of community effort on economic development in Nasarawa state, Nigeria. To this end, the research used data from primary sources of information. Data were collected by administering questionnaires. The sample size used in this study is 340 individuals drawn from three communities, (one community from each senatorial district Headquarter). The sample size was calculated by using Yamane (1967) formula. The study adopted ordinary least square (OLS) regression method to carry out the investigation. The data were collected from three (3) communities, one from each senatorial districts Headquarters in Lafia, Akwanga, and Keffi Local Government Areas of Nasarawa state, Nigeria. The results of the study showed that all the indicators of community efforts (educational development, health facilities, and road network) have positive impact on economic development (level of income) in communities in Nasarawa State. Therefore, it can be concluded that community efforts generally had positive impact on economic development (level of income) in communities in Nasarawa State. The study recommends that provision of more educational facilities by communities will help to develop a resilient population thereby leading to better performance of civil services in communities, and that provision of more health facilities by communities will create in-built resistance among the residents to epidemics caused by air, water, and changes in weather. Therefore, all stakeholders and hands must be on deck in the fight against illiteracy in communities so that Nasarawa state can join her members in enjoying the dividend of development experienced through education.